Morphoregression and Reproduction Aspect of Bonylip Barb (Osteochilus vitattus Valenciennes, 1842) in Tamblingan Lake, Bali Island - I Nyoman Yoga Parawangsa; Gede Arya Kusuma Artha; Prawira Atmaja Rintar Pandapotan Tampubolon (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight Research Morphoregression and reproduction aspect of bonylip barb was analyzed Fork length more accurately to estimate the body weight Lm50 of bonylip barb in Tamblingan Lake was 116 mmTL Growth pattern is isometric Good reproduction aspect   Abstract Bonylip barb (Osteochilus vitattus Valenciennes, 1842) is one of many native fish inhabiting Tamblingan Lake. The information about this species in Tamblingan Lake is rare which requires fulfilment in information gaps for the management of bonylip barb. The aims of this research were to find out the length-length relationship, length-weight relationship, length at first maturity, sex ratio, gonadal maturity stage, gonadosomatic index (GSI), fecundity, as well as spawning period and location in Tamblingan Lake. The fish sample was captured with experimental gillnet that was set in the afternoon and hauled in the next morning. Length and weight of every sample were taken. All samples were dissected to observe the sex and gonad. Fork length was the type of length with higher accuracy to estimate the body weight than the other length character. Growth pattern of this species was isometric. Lm50 of bonylip barb in Tamblingan Lake was 116 mmTL. Sex ratio of bonylip barb was imbalanced (1.00:0.82). Gonad maturity stage I-V was found during the research with GSI between 0.16-15.50 for male fish and 0.43-32.82 for female fish. The highest GSI was found in March, 15.50 for male fish and 32.73 for female fish. Mature fish were discovered in all stations in every month of sampling. The fecundity of bonylip barb ranged between 2,792-279,326 eggs. The length-length and the length-weight showed a strong relationship. The fish was isometric. Based on the growth pattern and the reproductive aspects, the population of bonylip barb in Tamblingan Lake was in good condition.